2020
DOI: 10.1093/femspd/ftaa064
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RT-PCR profile in 298 Indian COVID-19 patients: a retrospective observational study

Abstract: Background Despite being in the 5th month of pandemic, knowledge with respect to viral dynamics, infectivity and RT-PCR positivity continues to evolve. Aim To analyse the SARS CoV-2 nucleic acid RT-PCR profiles in COVID-19 patients. Design It was a retrospective, observational study conducted at COVID facilities under AIIMS, New Delhi. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
4
7
1
Order By: Relevance
“…Our study revealed that advanced age was associated with an increased risk of prolonged time to viral clearance, which is consistent with previous studies [ 19 , 22 , 23 ]. This could be attributed to the decline of T cell functions and proliferation with increasing age resulting in decreased control of viral replication and viral clearance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study revealed that advanced age was associated with an increased risk of prolonged time to viral clearance, which is consistent with previous studies [ 19 , 22 , 23 ]. This could be attributed to the decline of T cell functions and proliferation with increasing age resulting in decreased control of viral replication and viral clearance.…”
Section: Discussionsupporting
confidence: 93%
“…Diabetic patients also showed a significantly longer duration for viral clearance when compared with nondiabetic patients. However, Li et al [12,p.506–512] and Bhattacharya et al [23] showed a non-significant correlation between diabetes and viral shedding. And Hirai et al [19,p.864–868] showed a significant association between diabetes and a shorter time till viral clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, males predominated the symptomatic cases. Similar findings were reported by Xiao et al (2020) [10], Bhattacharya et al (2020) [11], and Alshukry et al (2020) [12]. The biological differences in the immune systems existing between males and females may influence the ability to fight infection including SARS-CoV-2, and that may be the reason for the male predominance in the study.…”
Section: Discussionsupporting
confidence: 89%
“…A period of 14 days' isolation is generally recommended throughout the world to prevent the spread of SARS‐CoV‐2. Increased age was positively associated with prolonged RT‐PCR positivity 8 . Although SARS‐CoV‐2 RNA shedding can be detected for an extended period, the duration of a live virus is relatively short‐lived 9 .…”
Section: Introductionmentioning
confidence: 97%
“…Increased age was positively associated with prolonged RT‐PCR positivity. 8 Although SARS‐CoV‐2 RNA shedding can be detected for an extended period, the duration of a live virus is relatively short‐lived. 9 In this study, we compared the duration of SARS‐CoV‐2 viral RNA in individuals with different Ct values and evaluated the dynamics of viral load in cases that required 15–30 days to clear SARS‐CoV‐2 viral RNA.…”
Section: Introductionmentioning
confidence: 99%